(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
According to some researches and sources,English is the most-studied language over the globe.Despite its prevalence,learners encounter complexities related to grammar,vocabulary and pronunciation,which,usually,lead them to relinquishment.In this condition,teachers should stimulate students to be resistant towards difficulties by making them interested in learning the language.